Electric vehicles narratives in public conversation: the underrepresentation of scientific knowledge in media coverage - S Rouli Manalu; Yohanes Thianika Budiarsa (Interaksi: Jurnal Ilmu Komunikasi)
This study examines the representation of electric vehicle (EV) issues in Indonesian mass media to understand how science, policy, and public discourse intersect in the context of sustainable transportation. Through a mixed-method content analysis of three major online news outlets—Kompas.com, Detik.com, and CNN Indonesia—spanning the years 2023–2024, the research reveals that media coverage is dominated by government narratives, focusing heavily on policy initiatives, subsidies, and market trends. Meanwhile, perspectives from civil society, academics, and environmental advocates remain underrepresented. Scientific information—particularly concerning EV lifecycle emissions, battery supply chains, and broader environmental trade-offs—is largely absent or presented without sufficient depth or balance. The study argues that the media must adopt a more inclusive, evidence-based approach to science communication to better inform the public, support democratic participation in policy-making, and promote informed societal engagement with Indonesia’s transition to sustainable transport.